2018
DOI: 10.1016/j.jbo.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of CCL2 enhances immunotherapeutic effect of anti-PD1 in lung cancer

Abstract: Myeloid derived suppressor cells (MDSC) play a pivotal role in tumor immune evasion and MDSC levels increased in patients with cancer. Studies confirmed the associations between MDSC and various cytokines in the peripheral blood. However, little is known about the association between parenchymal MDSC subsets and cytokines, or the mechanism drawing MDSC into tumor parenchyma. This study was to analyze the correlation between MDSC subsets and CCL2 level in lung cancer model. G-MDSC and M-MDSC from the blood and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 33 publications
0
41
0
Order By: Relevance
“…Anti-CCL2 treatment inhibits the expression of arginase 1 and iNOS, thereby reducing G-MDSC and M-MDSC in and around the tumor. Combination therapy can increase CD4 + and CD8 + T cell infiltration and prolong the survival of tumor-bearing mice [169]. Furthermore, the inhibition of HDAC6 significantly reduces HLA-DR-Low/CD11b + CD33 + MDSCs in the tumor microenvironment [156].…”
Section: Combination Therapeutic Strategy To Enhance T Immune Cell Fumentioning
confidence: 99%
“…Anti-CCL2 treatment inhibits the expression of arginase 1 and iNOS, thereby reducing G-MDSC and M-MDSC in and around the tumor. Combination therapy can increase CD4 + and CD8 + T cell infiltration and prolong the survival of tumor-bearing mice [169]. Furthermore, the inhibition of HDAC6 significantly reduces HLA-DR-Low/CD11b + CD33 + MDSCs in the tumor microenvironment [156].…”
Section: Combination Therapeutic Strategy To Enhance T Immune Cell Fumentioning
confidence: 99%
“…Wang et al showed that MDSC subsets had a positive correlation with CCL2. In addition, combination treatment with a CCL2 antagonist and anti-PD1 antibody enhanced CD4 + and CD8 + T cell infiltration, as well as the production of IFNγ, and increased the survival time of tumor-bearing mice [105]. KRAS mutations, known as oncogenic driver mutations, have been detected in 20~40% of adenocarcinomas and in 3~6% of squamous cell carcinomas [132].…”
Section: Increased Immune Checkpoint Inhibitor Efficacymentioning
confidence: 99%
“…Recent studies showed that the CCL2/CCR2 axis plays a vital role in the brotic formation in some diseases, including pulmonary brosis, renal brosis and nonalcoholic liver brosis, in addition to chemotactic macrophage in ltration [27,44,45]. It is found that CCL2/CCR2 axis was closely related to aggregation of myeloid-derived inhibitory cells (MDSCs) and inhibition of T cell function in pulmonary brosis and lung cancer [46]. The proportions of CD11C + CD206 + and CCR2 + macrophages in adipose tissues highly elevated in patients with NASH compared to healthy controls and to patients with fatty liver and CCR2 + macrophages were also correlated with NASH severity (44).…”
Section: Disscussionmentioning
confidence: 99%